已知点P在曲线C:y=
(1)求f(t)的解析式; (2)设数列{an}满足a1=1,an=f(
(3)在 (2)的条件下,当1<k<3时,证明不等式a1+a2+…+an>
|
(1)∵y=
,1 x
∴y′=-
,1 x2
∴切线方程为y-
=-1 t
(x-t),1 t2
与y=kx联立得:xA=
,令y=0,得:xB=2t,2t kt2+1
∵f(t)=xA•xB,
∴f(t)=
(k>0,t>1).4t2 kt2+1
(2)由an=f(
)得:an=an-1
,4an-1 kan-1+1
=1 an
=kan-1+1 4an-1
•1 4
+1 an-1
,k 4
设bn=
-1 an
,k 3
则bn=
-1 an
=k 3
(1 4
-1 an-1
)=k 3
bn-1,1 4
∵a1=1,
∴①当k=3时,b1=
-1=0,1 a1
∴{bn}是以0为首项的常数数列,
∴an=1.
②当k≠3时,{bn}是以1-
为首项,k 3
为公比的等比数列,1 4
∴bn=(1-
)(k 3
)n-1,1 4
解得an=
,3•4n-1 k•4n-1+3-k
由①②,得an=
.3•4n-1 k•4n-1+3-k
(3)∵an-
=3 k
-3•4n-1 k•4n-1+3-k 3 k
=3k-9 k(k•4n-1+3-k)
=
,3k-9 k2•4n-1+k(3-k)
∵1<k<3,
∴an-
>3 k
•3k-9 k2
,1 4n-1
∴a1+a2+…+an-3n-8k k
=(a1-
)+(a2-3 k
)+…+(an-3 k
)3 k
=
(1+3k-9 k2
+…+1 4
)+81 4n-1
=
[1-(4(k-3) k2
)n]+81 4
>
+84(k-3) k2
=
,4(2k+3)(k-1) k2
∵1<k<3,
∴
>0.4(2k+3)(k-1) k2
∴a1+a2+…+an>
.3n-8k k